MANAJEMEN KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS PESANTREN (Studi Kasus di Tarbiyatul Muallimien Al-Islamiyah Al-Amien Prenduan) - Moh. Rofie (Institut Dirosat Islamiyah Al-Amien Prenduan, 2017)
Curriculum management serves important role in educational institution. The institution will be lacking in direction without good management of its curriculum. One of prominent Islamic educational institution is TMI Al-Amien Prenduan. It has unique curriculum structure and management. This research is aimed to describe Pesantren based management of Islamic education curriculum in Senior High School of TMI Al Amien Prenduan. The research uses qualitative method and finds three main points. First, the planning process involves top executive in the school and also pesantren. This is aimed to maintain that programs being held in school are in line with the programs being held in boarding school, outside class activity. Second, the plan is well-implemented as what already being planned before. Some improvements take place, adapted to fit Islamic education curriculum. Third, evaluation is carried out in two different components, curriculum structure and student learning competence.Curriculum management serves important role in educational institution. The institution will be lacking in direction without good management of its curriculum. One of prominent Islamic educational institution is TMI Al-Amien Prenduan. It has unique curriculum structure and management. This research is aimed to describe Pesantren based management of Islamic education curriculum in Senior High School of TMI Al Amien Prenduan. The research uses qualitative method and finds three main points. First, the planning process involves top executive in the school and also pesantren. This is aimed to maintain that programs being held in school are in line with the programs being held in boarding school, outside class activity. Second, the plan is well-implemented as what already being planned before. Some improvements take place, adapted to fit Islamic education curriculum. Third, evaluation is carried out in two different components, curriculum structure and student learning competence.